Lublin University of Technology as a Partner of the Project: Modern Learning – Development of Didactic Potential of the University - Wac-Włodarczyk, A.; Billewicz, P. (Elektronika ir Elektrotechnika, 2010)
This article outlines some aspects concerning realization of the project entitled Modern learning – development of didactic potential of the university. Lublin University of Technology accessed the project, which is co-financed by the EU, in September 2008. According to the schedule, until March 2013 the aim of the project should be reached, what means that the process of education at LUT will be adjusted to the requirements of national economy and labour market. What is more, the quality of education will increase. A structure of the project was described, as well as methods of introducing particular modules. There were listed things which had already been done, together with some statistics and graphs presenting efficiency of the project. As a conclusion, there were described activities which have not already been done (or which are in progress), but crucial to the project. In general, those activities will not only determine new standards in the process of education and its quality, but also will affect and improve many formal and organizational issues at Lublin University of Technology.